THE ROLE OF GREEN PRODUCTS AND GREEN PACKAGING IN PURCHASE DECISIONS - Siti Mardiyah; Siska Vivi Anggraeni; Laily Muzdalifah (Universitas Nahdlatul Ulama Sidoarjo, 2022)
The contribution of this research is 1) to find out the role of Green Products related to Purchase decisions, 2) to know the role of Green Packaging related to Purchase decisions, and 3) to know the role of Green Products and Green Packaging to Purchase decisions. The form of research used is a quantitative research using a descriptive approach. This study used a purposive sampling technique using a questionnaire to collect primary data. The population in this study were residents of Prasung Village, Buduran District, Sidoarjo Regency. The total population of Prasung village is 5,589 people, with a research sample of 98 respondents. Based on the research results, the Green Product variable has no significant effect on Purchase Decisions, while the Green Packaging variable significantly affects Purchase Decisions. Together, green products and green packaging have a significant impact on purchase decisions.